2020
DOI: 10.12659/msm.920376
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Prediction and Verification of Qingluo Tongbi Formula to Reduce Liver Toxicity of Tripterygium wilfordii via UGT2B7 in Endoplasmic Reticulum

Abstract: The hepatotoxicity of Tripterygium wilfordii Hook. f. (TWHF) limits its clinic utilization. Qingluo Tongbi formula (QTF) was formulated based on a basic Chinese medicine theory. Previous studies have confirmed the safety and efficacy of QTF in treating rheumatoid arthritis. Therefore, we considered that TWHF could be detoxified based on its reasonable compatibility with QTF. We investigated the detoxicity mechanism of QTF in reducing the liver toxicity of TWHF. Material/Methods:We used network pharmacology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…LGT is classified as a toxic herb in the Chinese Pharmacopoeia (Chinese Pharmacopoeia Commission 2020), as it is known to be toxic to humans, rats, dogs, pigs, and insects, but non-toxic to sheep, rabbits, cats, and fish (Chinese Pharmacopoeia Commission 2020; Zhang et al 1984 ). Toxicity was reported for the gastrointestinal system (Liu et al 2018a ), the central nervous system (hypothalamus, midbrain, medulla, cerebellum, and spinal cord; Wang et al 2016 ), and the cardiovascular system (Wang et al 2020 ), while bleeding and necrosis of the liver were also observed (Li et al 2020b ). LGT is mainly used as a treatment for leprosy, rheumatoid arthritis, tuberculosis, and other chronic lung disorders (Chen 2001 ; Wang et al 2018 ; Song et al 2020a ).…”
Section: Resultsmentioning
confidence: 99%
“…LGT is classified as a toxic herb in the Chinese Pharmacopoeia (Chinese Pharmacopoeia Commission 2020), as it is known to be toxic to humans, rats, dogs, pigs, and insects, but non-toxic to sheep, rabbits, cats, and fish (Chinese Pharmacopoeia Commission 2020; Zhang et al 1984 ). Toxicity was reported for the gastrointestinal system (Liu et al 2018a ), the central nervous system (hypothalamus, midbrain, medulla, cerebellum, and spinal cord; Wang et al 2016 ), and the cardiovascular system (Wang et al 2020 ), while bleeding and necrosis of the liver were also observed (Li et al 2020b ). LGT is mainly used as a treatment for leprosy, rheumatoid arthritis, tuberculosis, and other chronic lung disorders (Chen 2001 ; Wang et al 2018 ; Song et al 2020a ).…”
Section: Resultsmentioning
confidence: 99%
“…The innovative, well-designed, and systematic safety studies should be carried out step by step to achieve a comprehensive exploration of morphology-molecular mechanisms-gene targets in drug toxicity. The continuous advancement of high-throughput sequencing, bioinformatics analysis, and network pharmacology [51,52] provide new research ideas for pharmacology and toxicology.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Qing Luo Tong Bi compound has demonstrated the ability to regulate UGT2B7 activity in the endoplasmic reticulum, thereby reducing the liver toxicity associated with Tripterygium wilfordii Hook. f. (M. Li, Wang, et al, 2020). The Tiao Wei Cheng Qi Tang compound has been observed to mitigate the intestinal absorption of rhein, consequently alleviating the toxicity associated with Rheum L. in vitro (Peng et al, 2018).…”
mentioning
confidence: 99%